POST-COVID-19 economic recovery from the perception of entrepreneurs (Revista de Investigaciones Universidad del Quindío, 2022)
Introduction: the pandemic caused by the COVID-19 virus had strong repercussions worldwide both in the health of the population and in the economy of the countries, Mexico was not the exception and being a Latin American country with structural and social lags carried from many years ago, the impact was greater.Objective: the purpose of the research was to know the perception of businessmen from a capital city in southeastern Mexico about the impacts that the pandemic produced on their companies and the requirements that they contemplate for post-pandemic economic recovery.Material and method: study carried out under a qualitative approach, through the positivist paradigm. The technique used was the virtual focus group.Results: The results reflect that the categories that reflect the greatest number of phrases expressed by the businessmen were: work, investments, academic preparation and government support.Conclusions: weaknesses and needs of the business environment and also of the educational sector were identified, since one of the main findings was the lack of knowledge and skills of human capital in matters such as technology management, marketing and administrative knowledge, as well as of attitude and commitment.
Keywords: Covid-19; economic recovery; companies